2013
DOI: 10.1371/journal.pone.0054218
|View full text |Cite
|
Sign up to set email alerts
|

Two Strains of Male-Killing Wolbachia in a Ladybird, Coccinella undecimpunctata, from a Hot Climate

Abstract: Ladybirds are a hot-spot for the invasion of male-killing bacteria. These maternally inherited endosymbionts cause the death of male host embryos, to the benefit of female sibling hosts and the bacteria that they contain. Previous studies have shown that high temperatures can eradicate male-killers from ladybirds, leaving the host free from infection. Here we report the discovery of two maternally inherited sex ratio distorters in populations of a coccinellid, Coccinella undecimpunctata, from a hot lowland reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
0
5
0
3
Order By: Relevance
“…Известно, что у божьих коровок только часть популяции бывает заражена симбиотическими бактериями. Бактерии часто теряются в популяции [9], если нет селективных факторов, способствующих их распространению. Было обнаружено, что зараженность Spiroplasma снижает жизнеспособность личинок A. bipunctata [24], в той же работе при инфекции Rickettsia и Wolbachia подобного эффекта не выявлено.…”
Section: материалы и методыunclassified
See 2 more Smart Citations
“…Известно, что у божьих коровок только часть популяции бывает заражена симбиотическими бактериями. Бактерии часто теряются в популяции [9], если нет селективных факторов, способствующих их распространению. Было обнаружено, что зараженность Spiroplasma снижает жизнеспособность личинок A. bipunctata [24], в той же работе при инфекции Rickettsia и Wolbachia подобного эффекта не выявлено.…”
Section: материалы и методыunclassified
“…Более 60 % видов насекомых заражены симбиотическими бактериями, часто нарушающими репродукцию хозяев [8]. У божьих коровок симбионты вызывают андроцид -смерть потомства мужского пола и, соответственно, сдвиг в соотношении полов потомства в сторону самок [9]. Божьи коровки семейства Coccinellidae особенно подвержены заражению симбиотическими бактериями, 13 из 30 изученных европейских видов божьих коровок заражены бактериальными симбионтами родов Wolbachia, Spiroplasma и Rickettsia [9].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…This organismal system appears ideal to investigate the role of associated viruses in the evolution of parasites because of the short generation time of host and parasite, the broad geographic range of the parasite that infect ladybeetle species on all continents, and because of the possibility to track variations in virus genome in experimental evolution experiments. Most interestingly, ladybeetles are also associated with a diverse array of bacteria including multiple members of the genus Flavobacteria , Rickettsia , Spiroplasma , and Wolbachia , that may be involved in ladybeetle defense against the parasitoid ( Hurst et al, 1994 , 1997 ; Weinert et al, 2007 ; Elnagdy et al, 2013 ). Using techniques developed previously to study the defensive role of aphid symbionts, the microbiome of ladybeetles could be manipulated using a combination of antibiotic treatments and microinjections.…”
Section: Parasite Biological Weapon Strategiesmentioning
confidence: 99%
“…Recently, it has been shown that Wolbachia frequency correlates with longitude, altitude, and annual mean temperature in mites [26]. On the contrary, for ladybirds, hot climate does not affect the distribution of Wolbachia and their effects on the host [3].…”
Section: Introductionmentioning
confidence: 99%